2000
DOI: 10.1109/55.843156
|View full text |Cite
|
Sign up to set email alerts
|

Improved performance and reliability of N2O-grown oxynitride on 6H-SiC

Abstract: This letter reports, for the first time, N 2 O-grown oxides on both n-type and p-type 6H-SiC wafers. It is demonstrated that the N 2 O-grown technique leads to not only greatly improved SiC/SiO 2 interface and oxide qualities, but also considerably enhanced device reliabilities as compared to N 2 O-nitrided and conventional thermally-oxidized devices. These improvements are especially obvious for p-type SiC MOS device, indicating that N 2 O oxidation could be a promising technique for fabricating enhancement-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…18 The initial results 14 on gate oxides annealed in 100% N 2 O were not encouraging as D it and the near-interface trap density were increased. Xu et al 19 reported a decrease in D it and an increase in oxide reliability for gate oxides directly grown in 100% N 2 O on 6H-SiC, compared to gate oxides annealed in N 2 O. This was also observed in 4H-SiC.…”
Section: Introductionmentioning
confidence: 80%
“…18 The initial results 14 on gate oxides annealed in 100% N 2 O were not encouraging as D it and the near-interface trap density were increased. Xu et al 19 reported a decrease in D it and an increase in oxide reliability for gate oxides directly grown in 100% N 2 O on 6H-SiC, compared to gate oxides annealed in N 2 O. This was also observed in 4H-SiC.…”
Section: Introductionmentioning
confidence: 80%
“…This agrees with values reported for both SiO 2 ͑Refs. 13 and 14͒ and alternate dielectrics on SiC 4,7,8,15. A parallel shift of the experimental capacitance curve towards the ideal flatband after FGA was attributed to a reduction in fixed charge.…”
mentioning
confidence: 88%
“…Intensive studies have been carried out on SiC MOS-based devices and it is crucial to have a high quality gate oxide deposited or grown between a metal electrode and a SiC substrate. NitridedSiO 2 has been widely employed as gate oxide in SiC MOS-based high power devices, owing to its low interface and slow trap densities, high reliability, and low leakage current [7][8][9][10][11][12][13][14][15][16][17][18][19]. Nevertheless, the maximum permissible electric field in SiC-based devices is restricted by the nitrided-SiO 2 due to its low dielectric constant (k = 3.9) compared to SiC (k = 9.7), as scaled by the Gauss's law at the interface [20].…”
Section: Introductionmentioning
confidence: 99%